PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA PADA KOMITMEN ORGANISASI DAN IMPLIKASINYA PADA KINERJA PENGELOLA ANGGARAN (Studi Empiris Pada Satuan Kerja Perangkat Daerah Pemerintah Kabupaten Tabanan) - Ayu Rustini, Ni Komang; Sadha Suardikha, I Made; Putra Astika, Ida Bagus (Buletin Studi Ekonomi; VOL.20.NO.2.AGUSTUS 2015 (PP 83-176), 2016)
The Impact of the Influence of Compensation, Work Environment on Organizational Commitment and Its Implications on the Performance of the Budget Managers. Periodic evaluation of the performance of budget managers in the public sector must be done to carry out consistently the principles of local financial management. This study was depeloved to obtain empirical evidence of the influence of compensation, work environment on organizational commitment and its implications on the performance of the budget managers. The study was conducted in 41 Regional Work Units (SKPD) in the Government Administration of Tabanan Regency. The number of respondents was 221 budget managers, chosen by Proportionate Stratified Random Sampling method. The analyzed data was primary data, using Path Analysis. Hypothesis testing results indicate that there were positive effects of compensation, work environment and organizational commitment on the performance of the budget managers. Furthermore, there were positive effects of compensation and work environment on the performance of the budget managers through organizational commitment.   Keywords: compensation, organizational commitment, performance of the budget managers, work environment
Keywords: compensation, organizational commitment, performance of the budget managers, work environment